Thermal Stability Threshold for Amyloid Formation in Light Chain Amyloidosis - Poshusta, Tanya L. (Molecular Diversity Preservation International (MDPI), 2013)
Light chain (AL) amyloidosis is a devastating disease characterized by amyloid deposits formed by immunoglobulin light chains. Current available treatments involve conventional chemotherapy and autologous stem cell transplant. We have recently concluded a phase III trial comparing these two treatments. AL amyloidosis patients who achieve hematological complete response (CR) do not necessarily achieve organ response regardless of the treatment they received. In order to investigate the possible correlation between amyloid formation kinetics and organ response, we selected AL amyloidosis patients from the trial with kidney involvement and CR after treatment. Six patients were selected and their monoclonal immunoglobulin light chains were characterized. The proteins showed differences in their stability and their kinetics of amyloid formation. A correlation was detected at pH 7.4, showing that less stable proteins are more likely to form amyloid fibrils. AL-T03 is too unstable to form amyloid fibrils at pH 7.4. This protein was found in the only patient in the study that had organ response, suggesting that partially folded species are required for amyloid formation to occur in AL amyloidosis.